2000
DOI: 10.1097/00007632-200006150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Assessment of Transoral Plate Fixation for Atlantoaxial Instability

Abstract: Experimentally, isolated anterior atlantoaxial plating was less stable than the combined reconstruction procedures. Transoral plate fixation according to Harms in combination with posterior wire fixation according to Brooks provided a failure load and stiffness equal to transarticular screw fixation according to Magerl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 29 publications
0
26
0
13
Order By: Relevance
“…This not only fully inherits the essence of a ''three-point'' fixation but also significantly enhances the ability to limit anterior-posterior motion because an additional atlas hook is used to further restrict the flexion motion of atlantoaxial articulation, as well as the bone graft between posterior arch of C1 and spinous process of C2 is able to restrict the extension motion, as previously descried [21]. More importantly, the author's previous biomechanical study [13] had showed that this technique results in minimal angular values for ROM and theoretically can provide the most excellent biomechanical stability, compared to several established fixation techniques, such as Gallie, alone TA, TA ?…”
Section: Discussionmentioning
confidence: 80%
“…This not only fully inherits the essence of a ''three-point'' fixation but also significantly enhances the ability to limit anterior-posterior motion because an additional atlas hook is used to further restrict the flexion motion of atlantoaxial articulation, as well as the bone graft between posterior arch of C1 and spinous process of C2 is able to restrict the extension motion, as previously descried [21]. More importantly, the author's previous biomechanical study [13] had showed that this technique results in minimal angular values for ROM and theoretically can provide the most excellent biomechanical stability, compared to several established fixation techniques, such as Gallie, alone TA, TA ?…”
Section: Discussionmentioning
confidence: 80%
“…From these data, the calculated workspace C2 in frontal plane between both vertebral arteries is 28.7±3.56 mm (22)(23)(24)(25) in males and 27.4±3.12 mm (21-32) in females. Interestingly, there was no trend towards a decreased distance between the mid-sagittalline C2 and medial border of VAG in elderly patients (see Graph 1).…”
Section: Resultsmentioning
confidence: 99%
“…7). The superior facet angle of lateral mass C1 was measured with 29.7±5.4 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) in males, 26.9±4.9 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in females [32], and 22.4±1.52 (16.5-29.2) on average [26], respectively (Figs. 3, 7).…”
Section: Atlasmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown high immediate postoperative stability values [31,32], which allow a consequent postoperative mobilization of the patients in a stiff collar. Stresses to the subaxial spine are reduced, because the fusion is limited to the atlanto-axial joint and therefore nodding movements are not limited.…”
Section: Discussionmentioning
confidence: 99%